Prognostic factors in obstetric cases which were admitted in ICU (periods of calm and epidemics) Location, evaluation & ways of resolving human errors - Michail Michailidou, Evangelia; Paulidou, Kyriaki; Papadopoulou, Niki; Kalogiannidis, Ioannis; Daniilidis, Angelos; Eskitzis , Panagiotis (Clinical Medicine And Health Research Journal, 2023)
It is widely accepted that the field of obstetrics and gynecology is one of the most challenging specialties, due to the high expectations regarding patients' safety, irregular working hours and great sense of responsibility surrounding it. Medical errors among obstetricians, midwives and nurses consist a significant problem which arises in this field. Numerous factors have been shown to affect the occurrence of obstetric errors. Not only is raising awareness of the potential causes of high importance, but it can also contribute to the reduction of adverse events and unfortunate patient outcomes.